2005
DOI: 10.1002/path.1768
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the NF‐κB targets BCL2 and BIRC5/Survivin characterizes small B‐cell and aggressive B‐cell lymphomas, respectively

Abstract: Nuclear factor kappa B (NF-kappaB) activation has been proposed as a cardinal feature of tumourigenesis, although the precise mechanism, frequency, relevance, and extent of NF-kappaB activation in lymphomas remain to be fully elucidated. In this study, expression profiling and tissue microarray studies of 209 and 323 non-Hodgkin's lymphomas (NHLs) respectively, including the most frequent sub-types of NHL, were employed to generate a hypothesis concerning the most common NF-kappaB targets in NHL. These analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 30 publications
9
102
0
2
Order By: Relevance
“…Our findings are in keeping with those of another study using CNIO OncoChip (cDNA microarray containing 6386 genes), which also found significant homogeneity among lymphomas of small lymphoid cells, including chronic lymphocytic leukemia, follicular lymphoma, mantle cell lymphoma, and splenic marginal zone lymphoma. 23 Our conclusion is also consistent with that of the only other study directly comparing apoptotic gene Po0.006 (Fisher's exact test).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are in keeping with those of another study using CNIO OncoChip (cDNA microarray containing 6386 genes), which also found significant homogeneity among lymphomas of small lymphoid cells, including chronic lymphocytic leukemia, follicular lymphoma, mantle cell lymphoma, and splenic marginal zone lymphoma. 23 Our conclusion is also consistent with that of the only other study directly comparing apoptotic gene Po0.006 (Fisher's exact test).…”
Section: Discussionsupporting
confidence: 91%
“…36 While BIRC5/ Survivin has been reported to be strongly expressed in chronic lymphocytic leukemia bone marrow by real-time reverse transcriptase polymerase chain reaction and immunohistochemistry, 16 Sugahara et al 37 employed real-time reverse transcriptase polymerase chain reaction and found that BIRC5/ Survivin was downregulated in most cases of chronic lymphocytic leukemia, supporting the results of a recent microarray study. 23 In addition, Granziero et al 16 reported that survivin was detected only in the pseudofollicules of chronic lymphocytic leukemia lymph nodes through immunohistochemistry. This inconsistency in BIRC5/Survivin levels may be explained by the different techniques and specimens used.…”
Section: Mcl1 Wasmentioning
confidence: 99%
See 1 more Smart Citation
“…As Bcl-2 is a target of nuclear factor-kappaB (NF-kB), which is involved in cancer metastasis and angiogenesis, 49,50 the activated Bcl-2 induces vascular endothelial growth factor (VEGF) expression in endothelial cells, resulting in the promotion of tumor angiogenesis. 51 The downregulation of Bcl-2 by AS Bcl-2 inhibits the activity of NF-kB and decreases the expression of VEGF, thereby inhibiting tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The cooperating effects of MYC and BCL2 in lymphomagenesis have been shown in many studies. [4][5][6][7][8][9][10][11][12][13][14] Numerous case series of MYC/BCL2 double-hit lymphoma are reported in the literature. [15][16][17][18][19][20][21][22][23][24] MYC/ BCL2 DHLs represent B10% of all lymphomas that otherwise resemble diffuse large B-cell lymphoma (DLBCL).…”
mentioning
confidence: 99%